Creative Savings Class By Utilizing Recycled Savings Case Study in Malaysia - Lasmiatun, Lasmiatun; Layla, Regita (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAI Al-Khiarat Pamekasan, 2024)
Creative class activities for 9 migrant children at SB AT-TANZIL Kampung Lindungan aim to motivate, develop children's creativity, and manage money properly and correctly. From this activity, it is hoped that children will be able to organize which items are useful and which items they want, as well as increase awareness of the surrounding environment. The method used in this activity is lecture and direct practice. The results of this activity show that children do not just learn about the value of saving, but also gain an understanding of the importance of recycling and environmental conservation. Children learn about patience and perseverance in collecting money little by little and feel satisfaction when they see their savings grow.